Evaluation of large animal models for preclinical studies of heart failure with preserved ejection fraction using clinical score systems - Li, Ke; Cardoso, Cristiano; Moctezuma-Ramirez, Angel; Elgalad, Abdelmotagaly; Perin, Emerson (Frontiers in Cardiovascular Medicine, 2023)
Heart failure with preserved ejection fraction (HFpEF) is characterized by a complex, heterogeneous spectrum of pathologic features combined with average left ventricular volume and diastolic dysfunction. HFpEF is a significant public health problem associated with high morbidity and mortality rates. Currently, effective treatments for HFpEF represent the greatest unmet need in cardiovascular medicine. A lack of an efficient preclinical model has hampered the development of new devices and medications for HFpEF. Because large animal models have similar physiologic traits as humans and appropriate organ sizes, they are the best option for limiting practical constraints. HFpEF is a highly integrated, multiorgan, systemic disorder requiring a multipronged investigative approach. Here, we review the large animal models of HFpEF reported to date and describe the methods that have been used to create HFpEF, including surgery-induced pressure overloading, medicine-induced pressure overloading, and diet-induced metabolic syndrome. In addition, for the first time to our knowledge, we use two established clinical HFpEF algorithms (HFA-PEFF and H2FPEF scores) to evaluate the currently available large animal models. We also discuss new technologies, such as continuous remote pressure monitors and inflatable aortic cuffs, as well as how the models could be improved. Based on current progress and our own experience, we believe an efficient large animal model of HFpEF should simultaneously encompass multiple pathophysiologic factors, along with multiorgan dysfunction. This could be fully evaluated through available methods (imaging, blood work). Although many models have been studied, only a few studies completely meet clinical score standards. Therefore, it is critical to address the deficiencies of each model and incorporate novel techniques to establish a more reliable model, which will help facilitate the understanding of HFpEF mechanisms and the development of a treatment.